2019
DOI: 10.1186/s13287-019-1395-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical process prior to cryopreservation of lipoaspirates maintains extracellular matrix integrity and cell viability: evaluation of the retention and regenerative potential of cryopreserved fat-derived product after fat grafting

Abstract: Background Cryopreservation of fat grafts facilitates reinjection for later use. However, low temperature and thawing can disrupt tissues and cause lipid leakage, which raises safety concerns. Here, we compared the cryopreservation potential of stromal vascular fraction (SVF) gel processed from lipoaspirate with that of fat. Methods Human SVF gel and fat were cryopreserved at − 20 °C without cryoprotectant for 1 month. Fresh SVF gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Moreover, we observed little fluctuation in the quality and volume of SVF-gel frozen for 5 and 15 days relative to controls, albeit at no statistical significance. These results suggested that SVF-gel had similar cell activity after cryopreservation for 5 days and cryopreservation for 15 days, consistent with results from previous in vitro experiments [20].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we observed little fluctuation in the quality and volume of SVF-gel frozen for 5 and 15 days relative to controls, albeit at no statistical significance. These results suggested that SVF-gel had similar cell activity after cryopreservation for 5 days and cryopreservation for 15 days, consistent with results from previous in vitro experiments [20].…”
Section: Discussionsupporting
confidence: 91%
“…Third, gel property is demonstrated by rheological data that the storage modulus G was higher than the loss modulus G . Finally, similar nomenclature has also been reported in other studies (Feng et al, 2019;.…”
Section: Discussionsupporting
confidence: 76%
“…Different from scaffold-based ADSCs treatment ( Li X. et al, 2019 ), this strategy allows overcoming the limitations associated with the enzymatic isolation of SVF cells from adipose tissue and the expansion of ADSCs, as well as the complex process of scaffold fabrication. In addition, a recent study reported that after cryopreservation at −20°C for 3 months without a cryoprotectant, the mechanically processed fat product SVF gel from human lipoaspirate maintained ECM integrity and ADSC viability as well as their multipotency ( Feng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the successful fat tissue regeneration found in grafts from younger donors, approaches for the old adults could focus on banking younger adipose tissue for later use. To do this, a previously reported cryopreservation protocol may be utilized, which allows the attainment of a nearly normal fat graft appearance after cryopreservation when compared with fresh fat grafts [ 46 48 ]. Preservation of adipose tissue at a younger age, when biological activity is greatest, could be ideal for future regenerative medicine applications.…”
Section: Discussionmentioning
confidence: 99%